Structural failures due to snow in Japan. Issue 4 (15th March 2019) - Abé, Masato; Nakamura, Kazuki; Shimamura, Makoto
Abstract : About half the area of Japan is subject to annual continuous heavy snow. Approximately 15% of the population lives in the area. In this paper, snow-induced failure and structural design of building roofs in Japan are reviewed. First, an overview of the characteristics of snowfall and structural design for snow load in Japan is given. Then, the snowstorm of 2014 is reported, which hit a region without snow zone designation in the design standard and caused many structural failures along with 26 deaths. The snow load for flat roofs for a general area where heavy snow is not expected was increased following this event. Investigation of the roof failure of a power plant due to compacted snow in 2015 is also reported. Compaction of snow due to melting in earlier winter caused excessive snow density compared to what had been expected, while judgement of snow-removal operation was based on a visual evaluation of snow depth. After these events, real-time estimation of snow load has been developed and implemented for a wide area using meteorological observation. Also, a simple snow-load-estimation method based on snow depth measurement is developed to assist judgement of a specific plant.